2016
DOI: 10.18632/oncotarget.12774
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 suppresses adipogenesis by activating Wnt/β-catenin signaling in vivo and in vitro

Abstract: Sirtuin 1 (SIRT1) regulates adipocyte and osteoblast differentiation. However, the underlying mechanism should be investigated. This study revealed that SIRT1 acts as a crucial repressor of adipogenesis. RNA-interference-mediated SIRT1 knockdown or genetic ablation enhances adipogenic potential, whereas SIRT1 overexpression inhibits adipogenesis in mesenchymal stem cells (MSCs). SIRT1 also deacetylates the histones of sFRP1, sFRP2, and Dact1 promoters; inhibits the mRNA expression of sFRP1, sFRP2, and Dact1; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 42 publications
1
73
0
1
Order By: Relevance
“…However, the main question that has to be addressed is whether Sirt1 plays any role in promoting bone formation. Without delving into the intricacies of this process, it is important to point out that it is a well‐established fact that the Wnt signaling pathway is integral to bone formation . Findings from several studies have demonstrated that there are several ways by which Sirt1 potentiates Wnt signaling, particularly in the bones .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the main question that has to be addressed is whether Sirt1 plays any role in promoting bone formation. Without delving into the intricacies of this process, it is important to point out that it is a well‐established fact that the Wnt signaling pathway is integral to bone formation . Findings from several studies have demonstrated that there are several ways by which Sirt1 potentiates Wnt signaling, particularly in the bones .…”
Section: Discussionmentioning
confidence: 99%
“…Without delving into the intricacies of this process, it is important to point out that it is a well-established fact that the Wnt signaling pathway is integral to bone formation. (39) Findings from several studies have demonstrated that there are several ways by which Sirt1 potentiates Wnt signaling, particularly in the bones. (40)(41)(42)(43) To illustrate, Sirt1 via epigenetic silencing, downregulates the expression of Wnt antagonists such as the secreted frizzled related proteins (SFRPs) and dickkopf (Dkk) protein, leading to increased availability of the receptors for Wnt ligands and subsequently stimulation of the downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte-specific Sirt1 deletion increased the adipogenic capacity of WAT in mice in response to chronic HFD as demonstrated by white adipocyte hyperplasia and hyperacetylation mediated activation of Ppar γ [115], and increased WAT mass [101], [115] even under normal conditions. In agreement, mouse embryonic fibroblasts derived from mice homo- or heterozygous for Sirt1 deletion, were shown to possess higher adipogenic capacity in cell culture [116], [117]. By contrast, treatment with pharmacological SIRT1 activators decreases WAT mass during HFD [71], [89], [90].…”
Section: Sirts and Parps In Adipose Tissue Function In Basal And Obesmentioning
confidence: 62%
“…In 3T3-L1 adipocytes genetic or pharmacological Sirt1 inhibition increased the expression of inflammatory cytokines upon tumor necrosis factor 1 alpha stimulation, whereas Sirt1 activation had the opposite effect [133]. In agreement, genetic or antisense oligonucleotide mediated Sirt1 deficiency in rodents leads to elevated inflammation characterized by increased macrophage infiltration and mRNA expression of inflammatory cytokines in WAT under normal [107] and HFD conditions [101], [115], [117], [134]. However, during long-term HFD adipocyte specific Sirt1 deletion reduced WAT inflammation in contrast to the other findings [115].…”
Section: Sirts and Parps In Adipose Tissue Function In Basal And Obesmentioning
confidence: 69%
“…Furthermore, the murine SIRT1 knockout repressed the generation of adipose tissue34 and glucose modulation35 . BMMs were transfected for 24 h with miR-506 inhibitor prior to treatment with RANKL and EX.…”
mentioning
confidence: 99%